Concomitant depression and suicide in patients hospitalized for mental disorders - Reyes Portocarrero, Bertha (2002)
Identify the characteristics, causes and suicidal risks of the depressive syndrome in hospitalized patients with mental disorders. Recommendations for the evaluation, therapeutics approach and family strategies.